VARIASI JUMLAH DAN JENIS KATALIS PADA PRODUKSI BAHAN BAKAR CAIR DARI LEMAK SAPI MENGGUNAKAN REAKTOR BATCH - Sutini Pujiastuti Lestari; Irawan Rusnadi1; Sahrul Effendy A; Arizal Aswan; Abdul Qosim Al Junaidi; Adella Rahmawati; Reviana Herezky Ningsih (KINETIKA, 2021)
As we know, growing energy needs are not comparable with the growing availability of fuel thinning day. Therefore it is necessary for an investigation to obtain alternative source of renewable energy by utilizing animal waste such as animal fat. Utilization of beef fat potential when processed into a fuel because it can reduces the environmental impact caused by NOx emmision. In this research the fuel is made of beef tallow using a batch reactor. The aim of this research was to obtain liquid fuel in accordance Indonesian standard and determine the effect of catalyst variations and its amount. Liquid fuel was made through several stages of preparation such as raw materials, the catalysts, catalytic cracking and also final analysis,diesel product. The result of this research that the density obtained is 0,83 – 0,89 gr/ml, viscosity 2,72 – 4,92 cSt, and flash point 47,8 – 63,5 °C.